Developing social entrepreneurs through business curriculum: a Canadian experience. (1st January 2011) - Calvert, Victoria; Jagoda, Kalinga; Jensen, Laurie
The authors propose a theoretical model suggesting that social entrepreneurial behaviours for business students may be developed through sequential exposure and experiential learning. It argues that by exposing students to CSR and sustainability in multiple functional classes, then enabling the development of creativity and innovation through projects with community organisations, that students will develop a predisposition to social entrepreneurship. Initial results indicate the leap to socially responsible actions is facilitated by coop terms whereby students create ventures, and that the students exhibit social entrepreneurship by creating ventures that require innovative solutions, while pursuing a social mission, with limited financing.